Vibriosis in floating marine cage-cultured food fishes - Mohamad, Nurliyana (2019)
Vibriosis is a bacterial disease that is caused by several species from the genus of Vibrio. It leads to economic losses among the cage-cultured marine fishes throughout the world, including Malaysia. The lack of epidemiological data on vibriosis in this country has hindered the development of efficient curative and preventive measures to combat the disease. This study aimed to determine the prevalence of Vibrio spp., to identify the risk factors, transmission, clinical signs and histopathological changes in infected fish, and to understand the antibiotic resistance profiles and distribution of virulence genes of Vibrio spp. isolated from cage-cultured marine food fishes. A cross-sectional and longitudinal study was conducted from December 2016 to August 2017, at a commercial floating cage farm located at Pulau Ketam, Klang, Selangor, Malaysia. Monthly samplings of Asian seabass, red snapper and hybrid grouper (giant grouper × tiger grouper) were carried out to isolate and identify Vibrio spp. At the same time, various biotic factors and environmental parameters of the sampling area were also determined. While sampling the fish, clinical signs and histopathological changes of fish naturally infected with vibriosis were noted. Pathogenicity study was carried out to further confirm the causal agent of disease in cultured fish. In addition, the possible transmission routes of Vibrio spp. in cultured fish were analyzed. Lastly, the distributions of virulence genes among Vibrio spp. were determined using PCR identification, while the antibiotic resistance patterns of the isolates were determined using disc diffusion method. The highest occurrence of Vibrio spp. was found in the hybrid grouper (59%), followed by Asian seabass (31%) and red snapper (28%). Nine species of Vibrio were recovered from cultured fish in this study, where 88.1% of the isolated Vibrio belonged to the Harveyi clade, followed by the Vulnificus (6.6%) and the Cholera (0.6%) clades. Fish mortality and size showed strong associations with the presence of some Vibrio spp. The water parameters were inconsistently correlated with Vibrio spp. in each fish species; the water SO4, salinity and rainfall exhibited strong correlation with certain Vibrio spp. in the cultured fishes. In addition, fluctuation of physico-chemical properties of water may also impose stress to the cultured fish, thus increase their susceptibility to Vibrio infection. Hybrid groupers naturally infected by Vibrio harveyi and V. alginolyticus displayed lethargy, excessive mucus production, fins rot, enlargement of spleens and generalize congestion of the brains and internal organs. Experimentally infected Asian seabass demonstrated similar clinical signs and histopathological changes as naturally infected hybrid groupers. Asian seabass infected with single V. alginolyticus and co-infected with both Vibrio spp. resulted in 100% mortality. However, concurrently infected fish demonstrated severe clinical signs and histopathological changes compared to single infections, indicating bigger impact brought by concurrent infections to cultured fish. In addition, pyrH gene sequences of 160 isolates of V. alginolyticus, V. campbellii, V. parahaemolyticus and V. harveyi recovered from cultured fish, wild fish, trash fish, fish fry, water and sediment were used to investigate the degree of relatedness and possible transmission existing between the isolated Vibrio spp. The population tree revealed the possible transmission from the newly introduced fish fry and wild fish into the cultured fish, while water also might possibly serve as a natural transmission medium of certain Vibrio spp. in this fish farm. Typical virulence genes produced by pathogenic V. harveyi were widely distributed among the 63 Vibrio spp. isolated from fish in various geographical regions of Peninsular Malaysia. Multiple antibiotic resistance (MAR) was exhibited in all Vibrio strains, particularly against ampicillin, penicillin, polypeptides, cephems, and streptomycin, where 75% of the isolates have MAR index of higher than 0.20. Host species and geographical origin showed no correlation with the presence of virulence genes and the antibiotic resistance pattern of the Vibrio spp. In conclusion, this study demonstrated a yearlong presence of Vibrio spp. in cultured fishes, where fluctuating water physico-chemical properties influenced the presence of certain Vibrio spp. Exposure of cultured fish to different Vibrio spp. may also resulted in synergistic interactions between the pathogens, thus increasing the severity of the infection. In addition, wild and fry fish could transmit the Vibrio spp. to the cultured fish in cage farm. Lastly, the majority of Vibrio spp. isolated exhibited multiple antibiotic resistances, which represents a real concern and warrants on-going surveillance. The data presented in this thesis offer an updated information on vibriosis in cultured marine fishes in Malaysia, which could help in future effective control measures and contribute to the insights on methods to prevent the disease in cultured fish.